2015
DOI: 10.1021/acs.langmuir.5b02708
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Three-Dimensional Reduced Graphene Oxide Film by Using the Langmuir–Blodgett Method

Abstract: The Langmuir-Blodgett method has always been traditionally utilized in the deposition of two-dimensional structures. In this work, however, we employed the method to deposit three-dimensional reduced graphene oxide layers using an unconventional protocol for the first time. This was achieved by carrying out the dipping process after the collapse pressure or breaking point, which results in the formation of a highly porous three-dimensional surface topography. By varying the number of deposition layers, the por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 52 publications
(100 reference statements)
0
17
0
Order By: Relevance
“…However, recent studies have shown that when used in porous thin‐films processed from flakes or introduced in polymer composites, graphene‐based materials can exhibit dramatically improved performance for neural stimulation. For instance, porous graphene oxide electrodes reduced by laser treatment and by the Langmuir–Blodgett method have been reported to be able to stimulate neural tissues with outstanding charge injection values between 1 and 3 mC cm −2 . Furthermore, new promising materials are expected to emerge from the very active research field of the supercapacitors, in which graphene‐based materials exhibiting very large active surface area are being developed achieving very high double layer capacitance.…”
Section: Graphene Materials For Next‐generation Neural Interfacesmentioning
confidence: 99%
“…However, recent studies have shown that when used in porous thin‐films processed from flakes or introduced in polymer composites, graphene‐based materials can exhibit dramatically improved performance for neural stimulation. For instance, porous graphene oxide electrodes reduced by laser treatment and by the Langmuir–Blodgett method have been reported to be able to stimulate neural tissues with outstanding charge injection values between 1 and 3 mC cm −2 . Furthermore, new promising materials are expected to emerge from the very active research field of the supercapacitors, in which graphene‐based materials exhibiting very large active surface area are being developed achieving very high double layer capacitance.…”
Section: Graphene Materials For Next‐generation Neural Interfacesmentioning
confidence: 99%
“…[7] Graphene has outstanding properties, including good (electro)chemical stability, high theoretical specific surface area (2630 m 2 g À 1 ), [8] and excellent electrical conductivity. [9] There are several ways to prepare graphene films, including spray coating, [10] blade-casting, [11] Langmuir-Blodgett assembly, [12] chemical vapor deposition, [13,14] evaporation of water, [15] and vacuum-assisted filtration. [16][17][18] Among these methods, the vacuum-assisted filtration method is a facile and straightforward technique to obtain self-standing graphene films.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as shown in Fig. 4(h) the surface roughness of the Hy-RGO LS films was estimated to be about 30.5 nm from the AFM topography, which is much less than the value reported in the literature (about 84.7 nm) for an LS film of RGO prepared from a methanol suspension 34 . This reduced surface roughness can be attributed to the stabilization of RGO sheets by the DMF that was used as the solvent in the current study.…”
Section: Resultsmentioning
confidence: 54%